How could the TRIZ tool help continuous improvement efforts of the companies? - Maia, Laura Costa (2015)
This paper objective is to explore TRIZ tool as a tool that could be helpful during Lean implementation, in particular, during the continuous improvement process efforts. Attending to the already published papers regarding Lean and TRIZ, at least since 2004, this synergy is viable and sustainable. This paper presents TRIZ principles and discusses their relation With Lean Production principles. Additionally, presents some TRIZ tools and explain how they can be useful in the context of the methodology in development to be applied in Textile and Clothing Industry.